2009
DOI: 10.1590/s0004-282x2009000300015
|View full text |Cite
|
Sign up to set email alerts
|

Benign childhood epilepsy with centrotemporal spikes: word and pseudoword discrimination

Abstract: -In the active phase of benign childhood epilepsy with centro-temporal spikes (BCECTS) there may be a fall in scholastic performance. Objective: To study lexical decision in children with BCECTS. Method: 42 children with BCECTS were compared with a control group with respect to their hits and response time in a visual discrimination of words and pseudowords task (DWPT). Results: The children with BCECTS had a lower percentage of hits for words and pseudowords and showed longer response times for pseudowords. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 21 publications
2
10
0
1
Order By: Relevance
“…However, individualized test scores on several sub-domains revealed a different aspect. Like many previous studies1,4,6,8,19-26), this study also revealed that 8 children (35%) had memory impairment, problems in VF, frontal executive dysfunction and attention deficits which led to poor academic performance. The language impairment in children with BRE and the acquired aphasia in Landau-Kleffner syndrome (LKS) indicate a large spectrum of interactions between language function and epilpsy.…”
Section: Discussionsupporting
confidence: 84%
“…However, individualized test scores on several sub-domains revealed a different aspect. Like many previous studies1,4,6,8,19-26), this study also revealed that 8 children (35%) had memory impairment, problems in VF, frontal executive dysfunction and attention deficits which led to poor academic performance. The language impairment in children with BRE and the acquired aphasia in Landau-Kleffner syndrome (LKS) indicate a large spectrum of interactions between language function and epilpsy.…”
Section: Discussionsupporting
confidence: 84%
“…So this study demonstrated that BECTS influences a language network that involves the more anterior, and therefore frontal cerebral regions (Lillywhite et al, 2009). Difficulties have also been reported in academic perfomances (Nicolai et al, 2007) and learning, with deficits in reading (Ay et al, 2009;Fonseca et al, 2009;Papavasiliou et al, 2005;Piccirilli et al, 2008;Staden et al, 1998) and spelling (Monjauze et al, 2005;Papavasiliou et al, 2005;Staden et al, 1998). Memory also seems to be negatively influenced by spikes in the centrotemporal area: there are reports of difficulties in short-term verbal memory (Danielsson & Petermann, 2009;Northcott et al, 2005;Weglage et al, 1997), visuo-spatial memory (Baglietto et al 2001; www.intechopen.com Danielsson & Petermann, 2009;Volkl-Kernstock et al, 2009) and long-term verbal memory (Northcott et al, 2005) as well as in the learning of verbal information (Croona et al, 1999;Staden et al, 1998).…”
Section: Neuropsychological and Behavioral Profilesupporting
confidence: 54%
“…In children with BECTS, regardless of the hemisphere in which the epileptic focus was located, there was no ear advantage as is expected in typical language lateralization (right ear advantage/left hemisphere advantage) [33]. In children with bilateral focus, some studies found no particular deficits [41], while other studies found specific impairments in attention [29], reading and language capacities such as in discrimination of words and lexical decision [49].…”
Section: Discussionmentioning
confidence: 89%